RESEARCH ON NUTRITION ATHLETE OF PETANQUE NORTH SUMATERA - Lily, LILIANA (ACPES 2017, 2017)
Nutrition is one of the factors that influences the achievement of Petanque athletes of NorthSumatra, so it is necessary to be considered and adjusted nutritional needs with physical activity duringthe training program.The aim of the study is to find about the nutritional status of Petanque athletes in The North ofSumatra in 2017.The research methodology is a descriptive method. The number of trial are fifteen peopleobtained through total sample techniques. The study was conducted at Petanque Dormitory HighSchool of Sport and Health Bina Guna Medan. Instrument used to see the athletes nutritional status isby using Body Mass Index (BMI) measurement which measured height, weight, and age of eachathlete. In addition, also carried out questionnaires to the athletes who contained about the diet, diet,resting patterns and family background. The result of questionnaire is useful as input of this research.Furthermore, the measurement results are calculated using the formula BMI and then thecalculation results are converted with BMI table to determine the nutritional status of athletes, whetherin the state of lack, normal or obesity.Based on the calculation results obtained that the nutritional status of athletes Petanque NorthSumatra is in the normal category of 93% (14 people), while 7% (1 person) is in the category ofobesity.